Short Selling and Stock Price Crash Risk - 정재만; 왕수봉 (선물연구, 2020)
This paper investigates short selling and stock price crash risk. We find that short selling is positively associated with one-month-ahead stock price crash risk, consistent with the literature showing that short sellers are informed traders. We attribute this prediction ability to the information short sellers receive from foreign investors with high levels of ownership in a firm. Our results shed light on policy issues regarding short selling regulation.
Keywords: Short Selling; Crash Risk; Foreign Ownership